Correlation of Endometrial Thickness and Endometrial Histology in Post-Menopausal patients - Muhammad Kaleem Akhter, Syeda Khadija, Nadia Majid, Humiara Yousaf, Usman Ali Rehman, Anam Iftikhar, Waqas Manzoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Endometrial carcinoma is one of the commonest gynecological tumors occurring more commonly in post-menopausal women presenting with post-menopausal bleeding. TVUS is a screening tool to stratify patients as high or low risk on the basis of endometrial thickness. Aim: To know whether the finding of TVUS needs to be correlated with the histopathology of endometrial biopsy sample before making any definitive diagnosis or not. Method: We conducted a systematic search by using Google Scholar as search engines to retrieve all the relevant data published from 2019 to 2021 while following PRISMA Statement. Results: Out of 1039 articles retrieved, only 6 articles were found that met the preset inclusion and exclusion criteria and of which there were 4 were prospective studies and 2 were retrospective in nature. Conclusion: TVUS is an excellent screening tool for endometrial cancer but the findings of TVUS needs to be correlated with histopathological findings of endometrial biopsy samples to make a confirm diagnosis.